Izbranniki i narod . Izbranniki i narod . Representatives and People . Избранники и народ - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Legends and truths about political leaders; relations between those in power and ordinary people. Featured in the program: Aliyev, Heydar Alirza oglu (Head of the Parliament of Azerbaijan) Contributors: Tochilina, Marina (Anchor) Вымысел и правда о жизни политических лидеров; взаимоотношения власти и народа. В программе участвуют: Алиев, Гейдар Алирза оглы (Председатель парламента Азебрайджана) Создатели: Точилина, Марина (Ведущий/Ведущая)